Makna Corporate Social Responsibility Bagi Manajemen Pabrik Gula PT Kebun Agung (Malang, Jawa Timur) - Oktarizal, Muhamad Asrul; Triyuwono, Iwan; Achsin, Muhammad (Jurnal Aplikasi Manajemen, 2014)
This research is a study at Sugar Factory of PT. Kebon Agung. The aim of this research is to find the meaning of Corporate Social Responsibility (CSR) for the management of Sugar Factory of PT. Kebon Agung. The research approach is qualitative approach with phenomenology research design. Phenomenology is used to find a meaning of a reality Generally. Researcher uses phenomenology to find the meaning of CSR for management Of Sugar Factory Of PT Kebon Agung . The data collection techniques done with interviews added some important documents and records. Key informants in this study are, Manager of Administration and Finance, Manufacturing Manager, Engineering Manager, Plant Manager, Head of Public Relations, and Commissioner. Finding of this research are CSR is defined as responsibility to the society, the environment, and the state. Responsibility to the society applied in the form of charitable activities, creating of job opportunities, and good cooperation with the sugar cane farmers. Environmental responsibility also applied by waste management, and using of compost in planting process of sugar cane. And the last is responsibility to the state is realized by participating in national development actively, one of realization is depress the price of sugar and increase the amount of sugar production.